Effect of lymphocyte mediators on macrophages in vitro. A correlation of morphological and cytochemical changes - Nath, Indira (1973)
Sephadex purified PPD and Con A induced mediator rich fractions (MRF) were applied to guinea-pig macrophages cultured in vitro. At varying times after the addition of the MRF, cells were removed from culture for morphological study and for cytochemical tests. Respiratory enzyme activity and lysosomal acid phos-phatase activity were estimated and the former was quantitated using an integrating microdensitometer. Early changes, 1 hr after MRF contact, were observed and subsequent alterations in activity up to 48 hr after the addition of MRF were also seen. These changes have been related to the inhibition of migration and subsequent `activation' of the macrophages which has been observed morphologically at times up to 3 weeks after MRF addition. It is suggested that alterations in the cytochemistry of the macrophages after MRF contact could help explain changes in the behaviour of the cells under these experimental conditions.